First records of cave-dwelling pseudoscorpions of the genus Ephippiochthonius Beier, 1930 (Arachnida: Pseudoscorpiones: Chthoniidae) from the Caucasus, with description of three new species from Abkhazia and taxonomic comments on the genus - Turbanov, Ilya S.; Kolesnikov, Vasiliy B. (Zootaxa, 2023)
Three new hypogean Ephippiochthonius species from karst caves of Abkhazia (Western Caucasus) are described, including detailed diagnoses and illustrations: Ephippiochthonius kovali sp. nov., E. vargovitshi sp. nov. and E. dbari sp. nov. These are the first cave-dwelling species of the genus described from the Caucasus. The taxonomic significance of the position of the intermediate setae ih3 and ih4 on the antiaxial side of chelal hand in the genus Ephippiochthonius is discussed. Based on this and other features, the heterogeneity of the tetrachelatus-group is demonstrated. Given the presence of seta ph3, the following new combinations are proposed for the species formerly assigned to Ephippiochthonius: Occidenchthonius kemza (Ćurčić, Lee et Makarov, 1993) comb. nov. from Pecina u Kozuvarskoj Glami Cave, Serbia and Occidenchthonius romanicus (Beier, 1935) comb. nov. from Comana, Romania (all ex Ephippiochthonius).